Support and holistic nursing care in people with chronic diseases nonadherent to treatment - Veliz-Rojas, Lizet (2016)
Introduction. Nursing supports continuously people in their process of adaptation to chronic illness, approach from which it is essential to incorporate holistic elements in the support and care in order to focus on the totality and integrity of the person and their environment . In this regard, this essay aims to reflect on the importance of accompaniment and holistic nursing care for people with chronic diseases adherent to their treatment. This debate is based on the concept of adherence of the World Health Organization and holistic, humane and transpersonal look Jane Watson, main theoretical references.Development. High levels of non-adherence in people with chronic non-communicable diseases constitutes one of the main challenges facing the nursing. Consider the person with CNCD as a whole that has a life story, emotions, experiences, values and cultural beliefs, is relevant to provide quality care and promote adherence.Conclusions. Incorporate holistic and humanistic look in nursing care and support for people with NCDs becomes a key strategy when promoting adherence and thereby improve welfare levels and control of these diseases.